Pengaruh Edukasi Menggunakan Media Buku Cerita terhadap Pengetahuan tentang Pemilahan Sampah pada Anak – Anak di SDN Merjosari 4 Kota Malang - Nafisah Azzahrohdinda Khosiatulloh; Jupriyono Jupriyono; Wandi Wandi; Pudji Suryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Waste segregation is crucial because each type of waste has a different decomposition time. Sorting waste from the very beginning makes the subsequent management process much easier. However, many people have not implemented it due to a lack of knowledge on how to sort waste properly. One way to improve this knowledge is through education using storybook media. Therefore, this study aims to determine the effect of education using storybook media on knowledge about waste segregation. The research employed a pre-experimental one-group pretest–posttest design to assess changes in knowledge before and after the educational intervention. The study population consisted of all fourth- to sixth-grade students totaling 84 students, with 46 respondents selected as samples using proportional random sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis using the Wilcoxon test with α = 0.05 indicated an increase in knowledge before and after the intervention, with an average knowledge score increasing by 28.54 from 58.55 in the pre-test to 87.09 in the post-test. The analysis results showed a p-value of 0.00, which was less than 0.05. This increase in knowledge indicates that storybook media are effective in delivering waste segregation information because they combine storytelling and illustrations that are appropriate for the cognitive developmental characteristics of elementary school students. Therefore, this study rejected H₀ and concluded that educational interventions using storybook media have a significant effect on improving elementary school students’ knowledge of waste segregation.